The application of vascularized stomach flap to repair postoperative biliary stricture. Issue 26 (June 2018) - Zeng, Jianping; Wang, Jing; Dong, Jiahong; Huang, Xiaoqiang; Xia, Hongtian; Xiang, Xin
Abstract : Abstract: Hepaticojejunostomy, which is the "gold standard" procedure for repairing postoperative biliary strictures, predisposes patients to reflux cholangitis from loss of sphincter of Oddi. The aim of this study was to assess the sphincter-preserving biliary reconstruction approach to repair postoperative biliary stricture. An autologous vascularized stomach flap was prepared and used to repair biliary defect caused by postoperative biliary stricture. Patient clinical data were analyzed retrospectively and long-term prognosis was evaluated based on the Lillemoe standard. Twenty-eight patients who underwent surgery from 2002 to 2010 were enrolled for the study. The original surgical procedure that caused biliary stricture consisted of patients having cholecystectomy (n = 22), biliary duct exploration (n = 5), and hepatectomy (n = 1). Eighteen (64%) of the 28 patients had previous repair surgery before being admitted. Based on the Bismuth level, 7 were classified as type I, 15 as type II, and 6 as type III. The mean length of biliary defect determined preoperatively by magnetic resonance cholangiopancreatography was 1.5 cm. The surgical procedure was successfully performed for all patients with a mean operation time of 261 ± 47.8 minutes. The postoperative complication rate was 10.7%, including minor bile leak (n = 2) and pulmonary infection (n = 1). There was no perioperative deaths. Two patients were absent during follow-up, and the remaining 26 patients had a mean follow-up period of 7.5 years (61–155 months). Twenty-four patients remained healthy during the follow-up period, while 2 patients (7.7%) had sporadic recurrent cholangitis that eventually resolved spontaneously. The overall long-term outcome rate was 92.3%. None of the patients had recurrence of stricture during the follow-up period. These results suggest that biliary repair using vascularized stomach flap could reduce reflux cholangitis and offer a satisfactory long-term outcome. This procedure could be a reliable method to repair postoperative biliary stricture with limited biliary defect.